1996
DOI: 10.1007/bf02285774
|View full text |Cite
|
Sign up to set email alerts
|

Change in goals and values of men and women from early to mature adulthood

Abstract: Changes in goals and values between early and middle adulthood were investigated using a longitudinal sample of women and their male partners. Measures designed to assess personality changes as described by Gutmann and Jung were coded from open-ended responses to questions about middle-aged subjects' concurrent and recollected goals and values. The findings indicated that both women and men declined in gender-traditional goals and values and increased in individual goals and values. Archival data for women sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Even though we did not specifically address the accuracy of people's aging perceptions, it is important to note that many studies have found considerable similarity between retrospective and concurrent perceptions of personality change (Harker & Soloman, 1996;Helson & Wink, 1992;Ryff, 1982;Stewart et al, 2001;Zucker et al, 2002). For example, Zucker et al (2002) found substantial overlap between concurrent and retrospective reports of feelings of identity certainty, confident power, generativity, and concern about aging (the domains examined in the present study).…”
Section: Retrospective Accounts Of Agingmentioning
confidence: 57%
“…Even though we did not specifically address the accuracy of people's aging perceptions, it is important to note that many studies have found considerable similarity between retrospective and concurrent perceptions of personality change (Harker & Soloman, 1996;Helson & Wink, 1992;Ryff, 1982;Stewart et al, 2001;Zucker et al, 2002). For example, Zucker et al (2002) found substantial overlap between concurrent and retrospective reports of feelings of identity certainty, confident power, generativity, and concern about aging (the domains examined in the present study).…”
Section: Retrospective Accounts Of Agingmentioning
confidence: 57%
“…The fact that Affiliation showed an unexpected trend-level relationship with the average child index for fathers may be influenced in part by the increase on Affiliation shown by many fathers between young adulthood and mature middle age (Wink & Helson, 1993). Theories of differences in parental personality emphasize the period when children are young, though some predict a lessening of gender differences in the parents' later adulthood (e.g., Gutmann, 1987), as was found in the Mills Study (Harker & Solomon, 1996;Wink & Helson, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…Koncepcja własnej osoby podlega dalszym modyfikacjom pod wpływem zadań rozwojowych i doświadczeń związanych z odgrywaniem nowych ról społecznych, a także postępującej zmiany rozwojowej w zakresie możliwości poznawczych, którymi dysponuje jednostka na różnych etapach dorosłego życia. W okresie wczesnej dorosłości kobiety i mężczyźni często zmieniają hierarchię celów i wartości (Harker, Solomon, 1996), które stanowią podstawę bardziej realistycznego w porównaniu z adolescencją, światopoglądu. Tożsamość młodych dorosłych kształtuje się przede wszystkim w kontekście dwóch obszarów doświadczeń: związanych z aktywnością zawodową oraz relacji społecznych, szczególnie w kontaktach intymnych.…”
Section: Zmiany W Tożsamości Człowiekaunclassified